2005
DOI: 10.1007/s11240-005-9020-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration of Alstroemeria cv. ‘Yellow King’ by direct organogenesis

Abstract: The common techniques for the in vitro production of Alstroemeria plants are based on rhizomes as explants, which have low multiplication rates and a high risk of carrying viral diseases. To overcome these problems, we developed a protocol for the in vitro regeneration of Alstroemeria cv.'Yellow King', by testing for shoot induction several explant sources (leaf, stem apices, rhizomes and immature inflorescence apices), temperature and light/dark regimes, hormone and salt concentrations. For shoot multiplicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In the present study, concentrations of BAP higher than 1.0 mg•l 1 caused a reduction in shoot number, similar to that reported by Pierik et al (1988). In the previous studies on Alstroemeria in tissue cultures, the use of BAP was effective for plant regeneration in most cases (Kim et al 2006;Lin et al 1997Lin et al , 1998Lin et al , 2000aPedraza-Santos et al 2006). However, in our study, BAP combined with IBA was effective for regeneration of Alstroemeria.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, concentrations of BAP higher than 1.0 mg•l 1 caused a reduction in shoot number, similar to that reported by Pierik et al (1988). In the previous studies on Alstroemeria in tissue cultures, the use of BAP was effective for plant regeneration in most cases (Kim et al 2006;Lin et al 1997Lin et al , 1998Lin et al , 2000aPedraza-Santos et al 2006). However, in our study, BAP combined with IBA was effective for regeneration of Alstroemeria.…”
Section: Discussionsupporting
confidence: 88%
“…For effective propagation, concentrations of growth regulators, especially cytokinins and auxins are crucial (Kalimuthu et al 2007). Pedraza-Santos et al (2006) demonstrated that the addition of 1 mg•l 1 BAP to the MS basal culture medium caused formation of up to 9.0 shoots per explant. In our experiment, an increase in BAP concentration from 0 to 1 mg•l 1 stimulated the increase of adventitious shoots number.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro propagation has been also considered to propagate alstroemeria since this technique has several advantages, particularly in terms of efficiency (Yousef et al, 2007;Pumisutapon et al, 2011;Seyyedyousefi et al, 2013;Hutchinson et al, 2014). Rhizome sections have been the most common explant used for the in vitro propagation of alstroemeria (Pumisutapon et al, 2012;Shahriari et al, 2012), although some experiments have also considered aerial explants such as stem (Kim et al, 2006), leaf (Nasri et al, 2013) and flower buds (Pedraza-Santos et al, 2006). In addition to the type of explant, characteristics of the culture medium are crucial to achieving successful micropropagation.…”
Section: Introductionmentioning
confidence: 99%